Self-esteem and psychosis in daily life: an experience sampling study - Daemen, Maud; van Amelsvoort, Therese; Reininghaus, Ulrich (Journal of psychopathology and clinical science, 2022)
Evidence suggests that self-esteem is an important mechanism in pathways to psychosis. However, whether low or high self-esteem is associated with psychotic experiences remains unclear. Besides, a limited number of studies has investigated fluctuations in state self-esteem in psychotic patients. This study investigated cross-sectional and temporal associations of momentary self-esteem and fluctuations in self-esteem with psychotic symptoms in three groups with different levels of (familial) liability to psychotic disorder. Using the Experience Sampling Method (ESM), momentary self-esteem, fluctuations in self-esteem (i.e., variability and instability), and psychotic experiences, paranoia, negative symptoms (i.e., event anhedonia and social anhedonia), intensity of negative affect and altered affective experiences (instability and variability in negative affect) were assessed in 147 psychotic patients, 131 of their siblings and 113 controls. Lower levels of momentary self-esteem were associated with an increased intensity of psychotic experiences, paranoia and negative affect, with the magnitude of the associations for momentary self-esteem being greatest in patients, followed by relatives. Variability in self-esteem was associated with psychotic and paranoid experiences, the magnitudes were greatest in relatives. Furthermore, we found reciprocal effects between momentary self-esteem and psychotic experiences, paranoia, negative affect, and instability in negative affect. These findings suggest that individuals with familial liability to psychosis (patients and their first-degree relatives) might benefit from targeting momentary self-esteem and variability in self-esteem to decrease the intensity of psychotic experiences, paranoia, and negative affect in daily life. (PsycInfo Database Record (c) 2023 APA, all rights reserved)